MANAGEMENT OF MEDICAL-SURGICAL NURSING CARE WITH SERVICE EXCELLENCE FOR MR. S WITH OPEN TIBIAL FRACTURE POST-ORIF IN ROOM RB 3 AT H. A DAM MALIK GENERAL HOSPITAL MEDAN CITY - Saruksuk, Joyvan; Sri Muliana Putri Bakara; Agung Purnomo; Rospika Girsang; Iin Nina Hastuti Padang; Dorlima Marito Hutapea; Roy S. Berutu (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Fractures are a condition characterized by the discontinuity of bone structure, which causes damage to the surrounding tissues. The chances of recovery are significantly higher when first aid is administered before the patient is taken to the hospital. There are various types of fractures, such as longitudinal, transverse, or mid-shaft fractures. These injuries are commonly accompanied by automatic tissue damage at the time the fracture occurs. According to a 2018 report by the World Health Organization (WHO), the prevalence of fractures reached 4.9%, with approximately 25 million cases recorded. In the previous year, 2017, there were 20 million cases with a prevalence rate of 4.2%. The number increased to 21 million cases in 2018 due to traffic accidents, although the prevalence slightly decreased to 3.8%. The latest data in 2022 showed a significant increase, with cases reaching up to 440 million worldwide. This study aims to provide an overview of medical-surgical nursing care for patients with fractures. The method used is a descriptive method, which aims to illustrate the ongoing phenomenon. The study includes a literature review with a nursing process approach consisting of assessment, diagnosis, planning, implementation, and evaluation. Based on the study results, the author provided medical-surgical nursing care to Mr. S, a patient who suffered an open tibial fracture following an ORIF (Open Reduction and Internal Fixation) procedure, for three days in Ward 3 at H. Adam Malik General Hospital. The results showed that the patient was able to use non-pharmacological techniques, such as deep breathing relaxation, to relieve postoperative pain. In addition, the issue of impaired physical mobility showed improvement through early mobilization carried out in stages.